Energy, exergy, environmental and economic analyzes (4E) and multi-objective optimization of a PEM fuel cell equipped with coolant channels. (April 2022) - Mei, Bing; Barnoon, Pouya; Toghraie, Davood; Su, Chia-Hung; Nguyen, Hoang Chinh; Khan, Afrasyab
Abstract: In the current research, the energy, exergy, environmental and economic (4E) analyzes of a PEM fuel cell are investigated. Parameters related to exergy are studied by considering the environmental effects and operating conditions of the PEM fuel cell. Multi-objective optimization is applied to maximize output power and efficiency and minimize environmental impacts and cost. The fuel cell is simulated with coolant channels and the effects of using porous metal foam inside the gas channels and coolant channels are investigated on the distribution of hydrogen and liquid water. The effect of using a hybrid nanofluid as a high potential liquid to keep the fuel cell cool is investigated. Optimal output power and optimal cost are provided according to the number of different cells. Optimal efficiencies (energy and exergy) and optimal environmental characteristics are likewise presented in a wide range of current densities. The results show that the simultaneous use of nanofluid and porous metal foam for cooling the fuel cell may not be appropriate. Furthermore, the effect of using metal foam is recommended for better cooling (increased heat transfer) of the fuel cell. Likewise, the use of porous metal foam inside the anode channel affects the distribution of hydrogen and liquid water. The effect of using porous foam in Re = 300 and above is significant so that in Re = 300, a 48% increase in heat transfer compared to the channel without porous foam can be seen. Besides, the percentage of reduction of nanofluid heat transfer in the presence of porous foam (in Re = 500) compared to pure water is 7.5%. Highlights: Energy, exergy, environmental and economic analysis (4E) of a PEM fuel cell is performed. Multi-objective optimization is applied to maximize output power and efficiency. Simultaneous use of nanofluid and porous metal foam for cooling may not be appropriate. Effect of using metal foam for better cooling is recommended. Use of porous metal foam inside the anode channel affects the distribution of hydrogen and liquid water.